Etiology and renal outcomes of acute tubulointerstitial nephritis: a single-center prospective cohort study in China. Issue 7 (17th August 2017) - Su, Tao; Gu, Yanghui; Sun, Pingping; Tang, Jiawei; Wang, Suxia; Liu, Gang; Li, Xiaomei; Yang, Li
ABSTRACT: Background: The aim of this study was to explore the etiology, long-term renal outcomes and affecting factors of acute tubulointerstitial nephritis (ATIN). Methods: Patients with biopsy-proven ATIN from 1 January 2005 to 31 December 2013 at Peking University First Hospital were enrolled in the study and received scheduled follow-up for at least 24 months. The causes of ATIN were defined at biopsy and reclassified during follow-up. Factors affecting renal recovery at 6 months post-biopsy and estimated glomerular filtration rate (eGFR) at 12 months post-biopsy and at the end of follow-up were analyzed. Results: A total of 157 ATIN patients were enrolled, with an average follow-up of 48 months (range 24–108 months). A modified etiology spectrum was identified, with a decreased proportion of drug-induced ATIN (D-ATIN, 64% at biopsy to 50% after follow-up) and an increase in autoimmune-related ATIN (22–41%) with late-onset systemic manifestations in patients who had been classified as D-ATIN or ATIN of unknown cause. Recurrent kidney injury was observed in 51% of the patients with tubulointerstitial nephritis and uveitis syndrome (TINU), 53% of those with an autoimmune disease and 8% of those with D-ATIN, resulting in prolonged immunosuppressive treatment. By 12 months, decreased eGFR (<60 mL/min/1.73 m 2 ) was observed in 47% of the patients with D-ATIN, 74% of those with TINU and 57% of those with other autoimmune diseases. In multivariable analysis, female sex, older age, presence of hypertension and recurrent kidney injury were independent risk factors for worse renal outcomes. Conclusions: Our data demonstrate that autoimmune-related ATIN may present with systemic manifestations after kidney injury and is, therefore, commonly misdiagnosed. Repeated kidney injury is not uncommon in patients with ATIN. Scheduled follow-up is, therefore, critical for defining the exact etiology and proper management of ATIN.